2019
DOI: 10.1088/1367-2630/ab413f
|View full text |Cite
|
Sign up to set email alerts
|

Optimal timescale for community detection in growing networks

Abstract: Time-stamped data are increasingly available for many social, economic, and information systems that can be represented as networks growing with time. The World Wide Web, social contact networks, and citation networks of scientific papers and online news articles, for example, are of this kind. Static methods can be inadequate for the analysis of growing networks as they miss essential information on the system's dynamics. At the same time, time-aware methods require the choice of an observation timescale, yet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
(100 reference statements)
0
3
0
Order By: Relevance
“…However, time interval selection is still an open subject. It directly affects the dynamics of simulated epidemics and information spread, mixing properties of random walk, synchronization on networks [9], and various analysis such as community detection [10,11], link prediction, attribute prediction, and change-point detection [12]. Recently, several studies are dedicated to find proper time intervals [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, time interval selection is still an open subject. It directly affects the dynamics of simulated epidemics and information spread, mixing properties of random walk, synchronization on networks [9], and various analysis such as community detection [10,11], link prediction, attribute prediction, and change-point detection [12]. Recently, several studies are dedicated to find proper time intervals [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…It directly affects the dynamics of simulated epidemics and information spread, mixing properties of random walk, synchronization on networks [9], and various analysis such as community detection [10,11], link prediction, attribute prediction, and change-point detection [12]. Recently, several studies are dedicated to find proper time intervals [10][11][12][13][14][15][16][17]. It is widely accepted that the system's time span should be divided into time intervals that are neither small enough to make the network noisy nor large enough to ignore significant time-dependent effects on the network [15,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In general, if we set one time step too long, we will lose a lot of detail; if we set one time step too short, the fluctuation may overwhelm the real signal. Recent research suggested that the timescale may also affect community detection [Medo et al, 2018]. To balance these effects, we choose one year as one time step, while the optimal choice of timescale remains an open question.…”
Section: Discussion and Outlookmentioning
confidence: 99%